Review: Groundwater research in the Ethiopian Rift Valley Lakes region - Hulluka, Taye Alemayehu; Balcha, Sisay Kebede; Yohannes, Biniyam; Bantider, Amare; Negatu, Adey (Frontiers in Water, 2023)
Despite its proximity to many research institutions in the country and prevailing environmental and water security challenges, water resources research in Central Rift Valley of Ethiopia has few decades of history. Research undertaken so far, mainly, focus on the lakes’ environment and anthropogenic activities in their proximities. However, current state of the central rift valley is a product of both anthropogenic and geogenic processes; happening within the sub-basin and its adjacent basins that need to be researched at a bigger thematic, spatial, and temporal scopes. The forefront environmental challenges and the need for quick fixes, lack of data, and funding are some of the limiting factors to limit the scope of research, mainly, to shallow groundwater zones and surface hydrological processes around the lakes. This approach has hindered seeing the bigger picture and resulted in ineffective environmental and natural resources restoration measures and policy decisions. Worsening deterioration of the water resources and environmental conditions; and the need to address overlooked but determinant natural and anthropogenic processes spurred critical review of what has been done so far. This work provides an overview of the history of water research in the central rift valley and tries to reveal research gaps related to surface water-groundwater interaction, water quality, and changing trends in the hydro ecosystem and possible causes. Apart from this, research dealing with the geological and structural setup of the central rift valley are reviewed to show their control over the hydrologic system. Keywords: Rift Valley Lakes, Ethiopia, groundwater, geological structures, wetlands